2016
DOI: 10.1038/ncomms12863
|View full text |Cite
|
Sign up to set email alerts
|

Platelet clearance via shear-induced unfolding of a membrane mechanoreceptor

Abstract: Mechanisms by which blood cells sense shear stress are poorly characterized. In platelets, glycoprotein (GP)Ib–IX receptor complex has been long suggested to be a shear sensor and receptor. Recently, a relatively unstable and mechanosensitive domain in the GPIbα subunit of GPIb–IX was identified. Here we show that binding of its ligand, von Willebrand factor, under physiological shear stress induces unfolding of this mechanosensory domain (MSD) on the platelet surface. The unfolded MSD, particularly the juxtam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
171
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(178 citation statements)
references
References 74 publications
6
171
0
1
Order By: Relevance
“…It should be noted that the soluble VWF-A1 used is able to bind GPIb on platelets 36 . Our results agree with the recent report that GPIb-induced platelet surface expression of CD62p requires force 28 . The low percentage shifting (<4%) of CD62p positive platelets in FACS reflects the widely accepted property of ADP as a weak agonist 29 .…”
supporting
confidence: 83%
“…It should be noted that the soluble VWF-A1 used is able to bind GPIb on platelets 36 . Our results agree with the recent report that GPIb-induced platelet surface expression of CD62p requires force 28 . The low percentage shifting (<4%) of CD62p positive platelets in FACS reflects the widely accepted property of ADP as a weak agonist 29 .…”
supporting
confidence: 83%
“…Under normal conditions, plasma VWF does not bind GPIbα. However, mutant VWF from patients with type 2B von Willebrand disease (VWD) exhibits heightened spontaneous binding to GPIbα and often leads to accelerated platelet clearance and thrombocytopenia 1215 . It was recently reported that binding of type 2B VWF, or botrocetin-induced binding of wild-type VWF, to platelets under physiological shear exerts a pulling force on GPIbα and induces unfolding of the MSD therein 15 .…”
Section: Introductionmentioning
confidence: 99%
“…However, mutant VWF from patients with type 2B von Willebrand disease (VWD) exhibits heightened spontaneous binding to GPIbα and often leads to accelerated platelet clearance and thrombocytopenia 1215 . It was recently reported that binding of type 2B VWF, or botrocetin-induced binding of wild-type VWF, to platelets under physiological shear exerts a pulling force on GPIbα and induces unfolding of the MSD therein 15 . MSD unfolding thereafter induces GPIb-IX signaling, including the elevation of intracellular Ca 2+ ([Ca 2+ ] i ), phosphatidylserine (PS) exposure and platelet desialylation, and accelerates platelet clearance 15, 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GPIb-IX complex detects this pulling and signals when the stalk of GPIba unfolds (see figure panel B). 5 This explained why antibodies must target the LBD of GPIba to activate and clear platelets, but did not explain why some antibodies target the GPIba LBD but cannot activate platelets. 3 Quach et al compare 2 antibodies, 6B4 and AK2, that both recognize the LBD of GPIba.…”
mentioning
confidence: 99%